Efectividad del secnidazol en el tratamiento de escolares asintomáticos parasitados por Giardia lamblia y/o Entamoeba histolytica - Simoes M; Rivero Z; Diaz I; Carreño G; Lugo M; Maldonado A; Chacín J; Parra M; Mendez Y; Del Villar A; Stern G (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2000)
ABSTRACT: introduction: The main goal in this study was to know the efficacy of treatment with Secnidazole in schoolchildren acting as asymptomatic carriers of Giardia lumblia and Entamoela histolytica and also to evaluate its toleration. Materials and Methods: A total of 50 children with parasitic disease (from 53 children with Entamoeba histolytica and/or Giardia lamblia) were chosen for the study, with ages ranking from 5 to 14, of either gender, to whom the drug was administered, and coproparasitological control tests were performed to them at third day of therapy. A question form was used to evaluate oral toleration to the drug. Result: From 53 cases studied, the protozoal ratio was as follows: Giardia lamblia 66.03%, followed by Entamoeba histolytica, 33.97 %. Parasitological effectiveness of Secnidazole against Gíardia lamblía was 100%, and against Entamoeba histolytica was 95.45 %. Only one carrier (4.55 %) did not respond to treatment. The drug had a good toleration in 50% of the cases. Most frequent symptoms were hyporexy, headache, abdominal discomfort/pair, dizziness, nausea, vomiting, diarrhea, drowsiness, taste sense anomal1e and itching. Conclusion: Efficacy and a relatively good oral toleration to Secnidazole was demonstrated in this study. Parasite absence was demonstrated after three days of trea1ment. RIESUMEN: Introducción: El propósito de la investigación es conocer la eficacia del Secnidazol en el tratamiento de escolares asintomáticos portadores de Giardia lamblia y/o Entamoeba histolytica, así como el evaluar su tolerancia. Material y métodos: Se escogieron 50 niños parasitados (totalizando 53 casos con Entamoeba histolytica y/o Giardia lamblia), con edades comprendidas entre 5 y 14 años, de uno u otro sexo, a quienes se les administró el medicamento y tres días después se realizaron exámenes coproparasitológicos controles. La tolerancia del medicamento se evaluó mediante encuesta. Resultados: De 53 casos parasitados, la relación de protozoarios fue: Giardia lamblia (66,03%) seguidos de Entamoeba histolylica (33,97%). La efectividad parasitológica del Secnidazol contra Giardia lamblia fue del 100% y de Entamoeba histolytica de 95,45%. Se obtuve un solo caso portador que no respondió al tratamiento (4,55%). El medicamento fue bien tolerado en el 50% de los casos. Los síntomas más frecuentes fueron: hiporexia, cefalea, dolor abdominal, mareos, náuseas, vómitos, diarrea, fatiga, alteración del gusto y prurito. Conclusiones: La eficacia y la relativamente buena tolerancia del Secnidazol fue demostrada en d presente estudie. Se obtuvo cura parasitológica al tercer día de administrado el medicamento.